2020
DOI: 10.1371/journal.pone.0228582
|View full text |Cite
|
Sign up to set email alerts
|

Women with fair phenotypes seem to confer a survival advantage in a low UV milieu. A nested matched case control study

Abstract: Background Sun exposure in combination with skin pigmentation is the main determinant for vitamin D status. Human skin color seems to be adapted and optimized for regional sun ultraviolet (UV) intensity. However, we do not know if fair, UV-sensitive skin is a survival advantage in regions with low UV radiation. Methods A population-based nested case-control study of 29,518 Caucasian women, ages 25 to 64 years from Southern Sweden who responded to a questionnaire regarding risk-factors for malignant melanoma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Vitamin D is produced in the upper epidermis through UVB‐induced catalysis of 7‐DHC into pre‐D, and it is required in the dermis to preserve NO production required for healthy vasodilation. This important function of vitamin D probably accounts for the intriguing finding of reduced all‐cause mortality in a large cohort of lightly pigmented Scandinavian women reported by Lindqvist and colleagues (Lindqvist et al., 2020 ). The role of vitamin D’s role in eNOS signaling, control of vasodilation, and regulation of blood pressure warrants further investigation in an evolutionary context with respect to the evolution of skin pigmentation under low UVR conditions (Wolf et al., 2020 ).…”
Section: Natural Selection and The Skin Of Early Homo Sapiensmentioning
confidence: 89%
“…Vitamin D is produced in the upper epidermis through UVB‐induced catalysis of 7‐DHC into pre‐D, and it is required in the dermis to preserve NO production required for healthy vasodilation. This important function of vitamin D probably accounts for the intriguing finding of reduced all‐cause mortality in a large cohort of lightly pigmented Scandinavian women reported by Lindqvist and colleagues (Lindqvist et al., 2020 ). The role of vitamin D’s role in eNOS signaling, control of vasodilation, and regulation of blood pressure warrants further investigation in an evolutionary context with respect to the evolution of skin pigmentation under low UVR conditions (Wolf et al., 2020 ).…”
Section: Natural Selection and The Skin Of Early Homo Sapiensmentioning
confidence: 89%
“…This conclusion finds further support in the results of a recent case‐control study performed on a sample of 24,000 Swedish women, which showed that women with red hair or freckles have a survival advantage in low UV environment. [ 33 ] It is possible that the positive effects of redheadedness prevail over this trait's negative effects only in high latitudes, for instance in Sweden and Scotland, countries situated largely north of the 55° parallel, [ 34 ] while in other parts of the world, they are sustained by gene flow [ 35 ] and/or sexual selection. [ 10,11 ]…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion finds further support in the results of a recent case-control study performed on a sample of 24,000 Swedish women, which showed that women with red hair or freckles have a survival advantage in low UV environment. [33] It is possible that the positive effects of redheadedness prevail over this trait's negative effects only in high latitudes, for instance in Sweden and Scotland, countries situated largely north of the 55° parallel, [34] while in other parts of the world, they are sustained by gene flow [35] and/or sexual selection. [10,11] The currently most popular hypothesis regarding the persistence of redheadedness and fair skin suggests that the decrease of eumelanin concentration in fair-skinned subjects and decrease of the eumelanin-pheomelanin ratio in redheaded individuals (who are mostly but not always fair-skinned) are an adaptation for synthesis of sufficient amount of provitamin D in regions with low, seasonally fluctuating intensity of UVB radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study of Swedish women with low-to-moderate sun exposure habits, women with fair phenotypes (the most UV-sensitive) had an 8% lower all-cause mortality rate than non-fair women, despite having a greater risk of dying from skin cancer. [5] Several biologically plausible mechanisms exist for a relationship between ultraviolet A (UVA) and ultraviolet B (UVB) exposure and positive health outcomes. UVB synthesises vitamin D in exposed skin.…”
Section: Introductionmentioning
confidence: 99%